RELEVANSI PEMBAGIAN WARIS ISLAM DENGAN KEADILAN SOSIAL DAN KONTEKS MASYARAKAT MUSLIM DI PURWOREJO - Rangga Wijaya, Djauhar; Andaryuni, Lilik (Al-Usroh : Jurnal Hukum Keluarga Islam, 2025)
The law of inheritance divides property for Muslims through a composition that is considered equal based on sharia, such as a 2:1 division between men and women. In the social system, there is a gap between men and women. This difference does not only occur in the household but also becomes a community culture. Habits that are still influential in people's lives both in rural and urban areas. This also affects the implementation of inheritance distribution. In the midst of social change and increasing awareness of gender equality, contemporary Muslim society in Indonesia has begun to question the relevance of these provisions, especially regarding the dual role of women in the domestic and public spheres. This study examines how the people of Purworejo Regency understand and apply Islamic inheritance law, as well as how the influence of social justice values in inheritance distribution practices. Using sociological and empirical juridical approaches, it was found that societies tend to combine Sharia principles with deliberation and grant approaches to achieve contextual justice. So that the distribution of inheritance using a 2:1 section needs to find a new opportunity, this is in line with the theory of social justice in contemporary society, where social justice provides equal rights for every individual, both male and female.